Healthy Captive Rose - Ringed Parakeets (Psittacula krameri) - Hematological and Biochemical Values - Oliveira da Paz Augusto Pinto, Gabriela; Saldanha, André; Scuissiatto de Souza, Giovana; Junior de Oliveira, Weslley; Carlos Beltrame, Olair; Alberto Cavazani de Freitas, Lineu; da Rocha, Chayane; Locatelli-Dittrich, Rosangela (Acta Scientiae Veterinariae, 2024)
Background: Rose - ringed parakeets are popular pet birds worldwide. This study aimed to determine hematological and biochemical reference intervals for healthy Rose - ringed parakeets to help in the monitoring and early detection of diseases, preserving the health of birds and humans. Materials, Methods & Results: Blood samples were collected from 58 healthy adult Rose - ringed parakeets (33 males and 25 females) aged 5 - 10 years. The birds’ health was assessed based on health history, physical examinations, and fecal examinations. Hematological and plasma biochemical analyses were conducted on the collected samples. The blood samples were collected from jugular vein with heparinized syringes. Blood smears were made immediately after the blood collection, and the samples were then packaged and sent to the laboratory. Hematological and biochemical analyses were performed within a maximum of 12 and 24 h after collection, respectively. The following biochemical profiles were analyzed: renal (uric acid), hepatic (GGT and AST), proteinogram (total protein, albumin, and globulin), muscular (AST, CK, and LDH), lipidic (total cholesterol and triglycerides), and electrolytes (calcium and phosphorus). Shapiro - Wilk test was used for normality analysis. The reference ranges were calculated using the package reference intervals R. The difference between males and females was analyzed using the Student t - test or the Mann - Whitney U test. The reference intervals for hematological parameters were as follows: RBC: 1.91 - 3.64 × 106/µL; PCV: 41.19% - 53.98%; HGB: 7.9 - 16.1 g/dL; MCV: 128.4 - 210.68 fL; MCH: 24.85 - 56.15 pcg; MCHC: 19 - 31.62 g/dL; WBC: 1.0 - 8.0 × 103/μL; heterophils: 0.134 - 4.678 × 103/μL; lymphocytes: 0.368 - 3.213 × 103/μL; monocytes: 0.033 - 1.440 × 103/μL; eosinophils: 0 × 103/μL; basophils: 0 - 0.760 × 103/µL; and heterophil:lymphocyte ratio: 0.12 - 2.97. The reference intervals for biochemical parameters were as follows: uric acid: 1.51 - 15.33 mg/dL; albumin: 1.04 - 2.64 g/dL; AST: 62.99 - 485.76 U/L; calcium: 6.79 - 10.18 mg/dL; CK: 321 - 3,279.51 U/L; total cholesterol: 191.15 - 446.49 mg/dL; phosphorus: 2.67 - 8.05 mg/dL; GGT: 7.2 - 29.37 U/L; globulin: 1.12 - 2.05 g/dL; LDH: 213.78 - 768.6 U/L; total protein: 2.7 - 4.2 g/dL; total plasma protein: 3.28 - 5.1 g/dL; and triglycerides: 41.1 - 502.02 mg/dL. No significant difference was observed between males and females for any parameters, except for the relative monocyte count, which was higher in males. Discussion: The results obtained in this study were based on a large number of birds. On erythrogram, differences between erythrocytes and hemoglobin were noted when compared with studies involving smaller populations (n = 16 and n = 20). These differences may be attributed to factors, such as age, breeding status, seasonal variation, and environmental factors. The hematocrit values were like another report with Rose - ringed parakeets (n = 16). On leukogram, the heterophils were more numerous, followed by lymphocytes. Eosinophils were rarely found. In the renal profile, uric acid values of 1.51 - 15.33 mg/dL were found, with no previous data specifically about uric acid in Rose - ringed parakeets but are considered within normal in birds range values up to 10 mg/dL. Higher values may have been influenced by the commercial formulated diet. On hepatic profile, GGT values were higher to that previously reported, but AST values were similar. On muscular profile, CK values were high and may be explained by physical restraint and containment stress. The lipidic profile (cholesterol and triglycerides) was influenced by diet, workout, climate, and hormones. Calcium and phosphorus values were higher than other reports. Calcium may vary with reproductive status, season. Diet may vary the phosphorus values. The values established in this report contribute to the diagnosis, control, and monitoring of diseases in Rose - ringed parakeets. Keywords: Ring - necked parakeet, psittacine, clinical pathology, avian, avian medicine, exotic pets.